Case report: Mafb promoter activity may define the alveolar macrophage dichotomy - Vo, Thao; Saini, Yogesh (Frontiers in Immunology, 2022)
Cre-LoxP system has been widely used to induce recombination of floxed genes of interest. Currently available macrophage promoter-specific cre recombinase mice strain have various limitations that warrants the testing of additional Cre strains. V-maf musculoaponeurotic fibrosarcoma oncogene family, protein b -Cre (Mafb-Cre) mice label macrophages in most organs such as spleen, small intestine, lung, bone marrow, and peritoneal cavity. However, whether Mafb-cre recombinase targets the gene recombination in alveolar macrophage remains untested. Here, we utilized MafbCre/WTR26mTmG/WT strain that expresses mTOM protein in all the cells of mice body except for those that express Mafb-cre regulated mEGFP. We performed fluorescent microscopy and flow cytometry to analyze mTOM and mEGFP expression in alveolar macrophages from MafbCre/WTR26mTmG/WT mice. Our analyses revealed that the Mafb-cre is active in only ~40% of the alveolar macrophages in age-independent manner. While Mafb- (mTOM+/mEGFP-) and Mafb+ (mEGFP+) alveolar macrophages exhibit comparable expression of CD11b and CD11c surface markers, the surface expression of MHCII is elevated in the Mafb+ (mEGFP+) macrophages. The bone marrow-derived macrophages from MafbCre/WTR26mTmG/WT are highly amenable to Cre-LoxP recombination in vitro. The bone marrow depletion and reconstitution experiment revealed that ~98% of alveolar macrophages from MafbCre/WTR26mTmG/WT  WT chimera exhibit are amenable to the Mafb-Cre mediated recombination. Finally, the Th2 stimulation and ozone exposure to the MafbCre/WTR26mTmG/WT mice promote the Mafb-Cre mediated recombination in alveolar macrophages. In conclusion, while the Mafb-/Mafb+ dichotomy thwarts the use of Mafb-cre for the induction of floxed alleles in entire alveolar macrophage population, this strain provides a unique tool to induce gene deletion in alveolar macrophages that encounter Th2 microenvironment in the airspaces.